The Potential for Engineering Enhanced Functional-Feed Soybeans for Sustainable Aquaculture Feed - Herman, Eliot M.; Schmidt, Monica A. (Frontiers in Plant Science, 2016)
Aquaculture is the most rapidly growing segment of global animal production that now surpasses wild-capture fisheries production and is continuing to grow 10% annually. Sustainable aquaculture needs to diminish, and progressively eliminate, its dependence on fishmeal-sourced feed from over-harvestedallocated fisheries. Sustainable aquafeed sources will need to be primarily of plant-origin. Soybean is currently the primary global vegetable-origin protein source for aquaculture. Direct exchange of soybean meal for fishmeal in aquafeed has resulted in reduced growth rates due in part to soybean’s anti-nutritional proteins. To produce an aquaculture soybeans for use in aquaculture feeds a new conventional line has been bred termed Triple Null by stacking null alleles for the feed-relevant proteins Kunitz Trypsin Inhibitor, lectin, and P34 allergen. Triple Null is now being further enhanced as a platform to build additional transgene traits for production disease vaccines, altered protein composition, and to produce high levels of -carotene an intrinsic orange-colored aquafeed marker to distinguish the seeds from commodity beans and as the metabolic feedstock precursor of highly valued astaxanthin.